THE IMPLEMENTATION OF CURRICULUM BASED INDONESIAN NATIONAL QUALIFICATION FRAMEWORK (KKNI) IN ISLAMIC EDUCATION STUDY PROGRAM AT THE ISLAMIC HIGHER EDUCATION IN MEDAN - Neliwati Neliwati; Derliana Marbun; Mahariah Mahariah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
This study aims to describe the Implementation of Curriculum Based on the IQF on PAI study program of FAI UMSU, PAI Study Program of FAI UISU and PAI study program of FITK UIN SU which includes three research focuses: Mechanism of curriculum change, curriculum development and compilation models, and KKNI based curriculum. This type of research is qualitative with a phenomenological approach. The instruments used in the study were observation, interviews, documentation studies and Focus Group Discussion (FGD). Analysis of the data used includes three steps: data reduction, data presentation and conclusion drawing. The results of this study indicate that: The KKNI-based lecture process carried out on the three study programs studied showed varied results. For PAI study programs of FAI UISU, lecture activities have not fully implemented the KKNI curriculum due to the absence of effective coordination between faculty leaders, study program leaders and lecturers to conduct lectures with the KKNI. Only a small proportion of PAI study program lecturers apply the KKNI. Furthermore, in the PAI study program of FAI UMSU, all lecturers have implemented the KKNI with the firmness of the leaders of higher education institutions, faculties and study programs as well as the supervision of the MONEV team (Monitoring and Evaluation) formed by the faculties and study programs. Besides that, the availability of adequate facilities that support lectures with the KKNI curriculum is also available. Meanwhile, in the PAI study program of FITK UIN SU, not all lecturers applies the KKNI curricula in their lectures. This is due to the lack of firmness and necessity of the study program to implement the KKNI, so that some lecturers do not apply it. Besides that, the lack of facilities and services that support lectures with the KKNI curriculum. Keywords:    Curriculum,  KKNI, Islamic Education Study Program(PAI)